“Child Labour: Issues and Challenges” - ., Trishnashree Devi (International Journal of Advanced Science and Technology, 2019)
Child labour and trafficking in children are the simple examples of deep rooted-problem of a society which has failed to protect and care for its children, a community that is either ignorant of the exploitation or does not feel shame in trading its children for gain. The scenerio with regard to problems of children has changed little despite continuous efforts made by the national and international agencies. Moreover, more and more serious steps should be taken in the developing countries to combat problems of children like child labour etc. This paper tries to give a detailed account of child labour in a broad perspectives. It also tries to discuss about the root causes of child labour and tries to give an account of international and national laws that tries to protect children rights.